(3OQGSGJ GdLOhi GdEbJUGOjI hJbjje GdeTQhYGJs - (3ghTjGQ(B, (3eYQhas ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY(B,s, 2004)
(3CSGSjGJ OQGSGJ GdLOhi hJbjje GdeTQhYGJ(B- (3CfhGY OQGSGJ GdLOhi hGdQHMjI GdeSJgOaI(B- (3JMdjd GdeYdheGJ GdCSGSjI dOQGSGJ GdLOhi hJbjje GdeTQhYGJ(B- (3eYGjjQ GdLOhi GdEbJUGOjI hJbjje GdeTQhYGJ(B- (3CSGdjH heDTQGJ Jbjje GdLOhi GdEbJUGOjI(B- (3EYOGO JbGQjQ GdLOhi hYQV MGdGJ JWHjbjI(B.s
(3GdeQGLY U(B.288s
Keywords: (3EOGQI GdeTQhYGJs; (3GdJMdjd GdEbJUGOjs; (3Jbjje GdeTGQjYs; (3OQGSGJ GdLOhis